Combating discrimination through Big Data – future of equality? - Sakolciová, Sandra; Máčaj, Adam (Vilnius University Open Series, 2020)
The paper aims firstly to assess the future of anti-discrimination measures and policies, above all through the lens of ethnic data utilization. The question posed is not only whether massive collection and usage of such data is viable in relation to its result, but also whether such ethnic data collection is an obligation incumbent upon state authorities, in international and European human rights protection systems in particular. On the other hand, this article aims to compare existence of such obligation with the existing standards on right to privacy and implications for this right stemming from such use of Big Data. The negative impact resulting from such obligation in this regard could weigh heavily on protection of personal data, currently one of the main concerns throughout Europe and the EU.